Continuous Supply to Load by Automatic Switchover in System During Fault Condition using PLC and SCADA - Ghimire, Amrit; Oliya, Ashish; Itani, Manmohan; Gyawali, Pawan; Bastola, Prakash; Pandey, Ram Prasad; Bhattarai, Samriddhi (Journal of Engineering and Sciences, 2022)
Abstract available with the full text.